Negative automatic thoughts as a mediator of the relationship between depression and suicidal behaviour in an at-risk sample of Malaysian adolescents - Choon, Min Wai; Abu Talib, Mansor; Yaacob, Siti Nor; Awang, Hamidin; Tan, Jo Pei; Hassan, Sallahuddin; Ismail, Zanariah (Wiley-Blackwell Publishing, 2015)
Background This study examined the mediating role of negative automatic thoughts in the relationship between depression and suicidal behaviour in a sample of at-risk Malaysian adolescents. Method A total of 1441 adolescents were initially recruited via multistage cluster sampling. Subsequently, 294 at-risk adolescents were selected for further analyses through a specified cut-off score. Results The results showed significant positive relationships among the study variables. Specifically, negative automatic thoughts emerged as a significant mediator in the relation between depression and suicidal behaviour (z = 7.15, p < .001). Conclusions The findings suggest that depressed adolescents are at high risk for a host of negative thought processes which in turn lead to suicidal behaviour. The study limitations and recommendations for further research are discussed.